Przedmioty objęte obowiązkiem zakat i dostosowanie obowiązku do warunków współczesnych – wybrane przykłady - Sadowa, Katarzyna (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The subject of this publication is the third pillar of Islam – zakat. The author focuses on the analysis of products which are covered by the obligation of paying zakat. Each of the category of such products is characterized and the amount of zakat for each of them is showed. While detailed rules regarding zakat of basic types of goods are included in sunna, there are some controversy about modern products which have not been known in the times of Prophet Mahomet. Therefore the author presents chosen examples of adaptation of such sunna’s rules to modern times.
Keywords: islam; filary islamu; trzeci filar; jałmużna; muzułmanie